RECONNAISSANCE HYDROCARBON GEOLOGY OF THE ANADYRSKY, KHATYRSKY, AND PENZHINSKAYA GUBA CENOZOIC SEDIMENTARY BASINS, NORTHERN KAMCHATKA PENINSULA, RUSSIA - Harbert W.; Sokolov S.; Heiphetz A. (My University, 2003)
In northeastern Russia, reconnaissance analysis of the Anadyrsky and Khatyrsky sedimentary basins indicates that oil and gas fields were formed where strata of potential reservoir quality are present, and faults or zones of high permeability connect the source rocks to zones where impermeable strata overlie reservoir formations. Upper Cenozoic rocks, which have been subjected to Paleocene to Quaternary tectonic reactivation, the degree of which generally increases southward within individual basins, contain known oil and gas deposits in these basins. The formation of these basins is the result of extension and rifting along the northwestern edge of the Kamchatka Peninsula, specifically in the Penzhinskaya Guba region. William Harbert completed his B.S. degrees at Western Washington University and his M.S. degree in exploration geophysics and Ph.D. in geophysics at Stanford University (1987). He has traveled extensively in Russia during 11 visits beginning in 1985. He is presently the chairman of the Department of Geology and Planetary Science at the University of Pittsburgh.Sergei Dmitrievich Sokolov earned his Candidate of Geological and Mineralogical Sciences (1975) and Doctor of Science in Geotectonics (1989) degrees at the Geological Institute of the Russian Academy of Sciences. He is presently the director of the Laboratory of Oceans and Peri-Oceanic Zones at the Geological Institute of the Russian Academy of Sciences, Moscow, studying accretionary tectonics, terrane analysis, and paleotectonic reconstructions. Alexander Heiphetz earned his B.S. and M.Sc. degrees in geology from Moscow University (1985). He worked in Russian academic insitutions studying geology and paleomagnetism of Kamchatka, Koryak Highlands, and Komandorskiy Islands. After earning his Ph.D. in geophysics from the University of Pittsburgh in 1995, Heiphetz worked for GeoMechanics. Since 1997, Heiphetz has run his own consulting and software company.
Keywords: Cenozoic; Cenozoic; Кайнозой